Remission from nicotine dependence among people with severe mental illness who received help/services for tobacco/nicotine use. Issue 4 (18th September 2020) - Alghzawi, Hamzah; Trinkoff, Alison; Zhu, Shijun; Storr, Carla
Abstract: Objectives: A growing body of evidence supports pharmacological interventions to assist smoking cessation in people with severe mental illness (SMI); that is, lifetime major depressive disorder, bipolar disorders, or schizophrenia. Little is known about whether behavioral services are also associated with high probability of remission from nicotine dependence as compared to other types of help/services received (pharmacological, behavioral, or both). Methods: A sample of 726 American lifetime adult smokers with SMI and a history of nicotine dependence, who received help/services for tobacco/nicotine use, were identified. These data came from a limited public use dataset, the 2012–2013 NESARC‐III. Survival analysis was used to compare the probability of remission from nicotine dependence and the time needed for full remission from nicotine dependence by type of help/services received for tobacco/nicotine use. Results: Remission was more frequent among those who received behavioral services. In addition, the average time from onset of nicotine dependence until full remission from nicotine dependence was shorter among those who received behavioral services. Conclusions: The current study suggests a clinical need for behavioral interventions to promote the probability of remission from nicotine dependence among smokers with SMI. Health care providers could play a role in educating and encouraging smokers with SMI to seek and utilize behavioral services.